-.6x+.5x+9=-3 -.1x=-12 x=120
To solve the equation 6x plus 4-3x,first subtract 3x from 4 which leaves you with 1x. The equation now reads 6x plus 1x, which equals 7x. --- Actually, to simplify this, we have to keep the numbers multiplied with the variables from the plain numbers. The equation based on the question it this: 6X + 4 - 3X So there is a +6X a -3x and a +4. So we simplify by consolidating the numbers multiplied with the Xs. So 6X - 3X is 3X. So we have 3x + 4. There is no way to solve this since we have only part of it and no equal sign.
bringing across the =, 5x = -10 so x = -2
x2 + 6x + 8 = 0 Solve for x.X = -2 or X = -4
16x+9 without the rest of the equation, what this equals, I can't solve
If 6x + 10 = 11x , then x=2.
6x + 8 = 13, 6x = 13 - 8, 6x = 5, x = 5/6
The answer is x = 2.
4x+3x-1x = 12 Collect like terms: 6x = 12 Divide both sides of the equation by 6 to find the value of x: x = 2
If we recall that (5 cows plus 1 cow) = 6 cows, it immediately becomes apparent that5x plus 1x = 6x.
It is not possible to solve a single linear equation in two variables.
5x + x = 5x Squared (5x^2) x + x equals 2 x's = 2 = squared - very simple & logic. no its not simple and logic 5x^2 is the result of 5x times x. 5x plus x is 6x. Think of the x as 1x not x so 1x + 5x= 6x. That's simple and logic.
2x - 6x + 3x = -412x - 3x = -41-1x = -41x = 41
2x+6x=-9 => 8x=-9=> x=-8/9
6x +108=18y y=6x/18+108/18 y=x/3+6
-6x + 12y = -102 -6x = -12y - 102 x = 2y + 17
6x+2y=4 gives y=2-(1/3)x
It works out that x = 6 and y = 3 or as (6, 3)
-4x+3 = 23+6x -4x-6x = 23-3 -10x = 20 x = -2
x = 6 and y = -2